US Financial Sector as a Reflection of Changes in the Prices of Shares of Leading Banks - Bril, M.; Kolomiiets, Y. Y.; Lyashenko, V. (IJARW, 2023)
Market relations cover all areas of economic dynamics; help the interaction of different business entities. This transforms the traditional prevalence of either only the banking sector of the economy or only the stock market. Positive changes are ta king place that are transforming the financial sector. This leads to the need for new research, taking into account the territoria l and temporal aspects of assessing the dynamics of the respective markets. Based on this, the paper considers the US financial sec tor. For these purposes, we consider key market shares that reflect the dynamics of the functioning and development of leadin g banks. The analysis is carried out using classical statistical approaches. As separate characteristics of such consideration, quotat ions for bank shares and the volume of sales of these shares are studied. We also use wavelet coherence estimates to consi der the mutual dynamics of the data, which helps to better understand the ongoing processes in the US financial market. The work presents a lot of graphs and diagrams, wavelet coherence estimates. This makes it possible to evaluate the reliability of the o btained results.
Keywords: economic dynamics; wavelet analysis